Knowledge Sharing Perpustakaan UIN Sunan Kalijaga Yogyakarta dengan Perpustakaan Sekolah - Ida Nor'aini Hadna (Asosiasi Perpustakaan Perguruan Tinggi Islam Wilayah Jawa Timur (APPTIS Jatim), 2019)
This paper was written with the aim of knowing the knowledge sharing activities carried out by the Sunan Kalijaga UIN Library to help develop the school library. The method that will be used is the best practice method. At present the condition of school libraries in Indonesia is still a concern. Some of the reasons that cause school libraries have not been able to carry out their duties and functions properly are the lack of understanding or comprehension of the essence of the library as an infrastructure in providing information, both from the principal, teachers, and students; library managers are not optimal in providing services, especially in order to meet the information needs of users; and the communication between the school library and the user community is poorly maintained. Facing various obstacles that are still faced by many school libraries, it is our duty to jointly build and develop school libraries to support better teaching and learning processes. Based on this, the Library of UIN Sunan Kalijaga also tries to help develop school libraries by doing knowledge sharing with the school library. The conclusion of this study is that there are changes that occur after the implementation of knowledge sharing programs, including the improvement of libraries in terms of increased attention from the leadership towards library development, library space conditions, teacher and librarian cooperation, library collections, level of student visits to libraries and librarian creativity.